The drowned soil: effects of an Icelandic hydropower reservoir on the soil carbon resource after 24 years of flooding - Möckel, Susanne Claudia; Bonatotzky, Theresa; Erlendsson, Egill; Álvarez, Ivan Rodrigo Casasola; Mankasingh, Utra; Gísladóttir, Guðrún (Frontiers in Environmental Science, 2025)
Increasing energy demand propels the construction of river dams and reservoirs for hydropower, raising concerns about environmental and societal ramifications. Ecological effects like river fragmentation, habitat loss, biodiversity decline, and disruptions of biogeochemical cycles have been addressed for several decades. The impact of water impoundment on submerged soils, particularly carbon stocks, is of growing interest. Studies reveal both increases and decreases of carbon stocks in submerged soils, depending on factors such as substrate resilience, water level fluctuations, soil type and submergence duration. This study examines the effects of 24 years of water impoundment on properties of organic and mineral constituents in Andosols under the Blöndulón hydroelectric reservoir in Iceland´s highlands. Submerged soils show higher carbon stocks than reference soils but are depleted in pedogenic minerals ferrihydrite and allophane. Unlike reference soils, where carbon declines with depth, submerged soils display rather uniform carbon distribution. This is likely due to movement of organic material from upper to lower horizons, and carbon additions from decaying vegetation in the years after the impoundment. Importantly, the apparent carbon enrichment of the submerged soils raises concerns about its long-term stability. The depletion of pedogenic minerals ferrihydrite and allophane may render the carbon sensitive to oxidation in the coming decades, particularly when soils are exposed during water level fluctuations. In short, the carbon enrichment of the drowned soils may not be permanent. Assessments of the consequences of water level fluctuations or potential future dam removal need to take the vulnerability of the exposed soils into account and consider the risk of increased carbon emissions from these soils.